Perancangan Model dan Prototype Aplikasi Tracer Study Berbasis Mobile - Dilson Dilson; Noviardi Noviardi (Prosiding SISFOTEK, 2018)
Difficulties Academic and Student Affairs Affairs in collecting data of alumni who have or have not worked and the amount of costs required to obtain alumni data is one of the problems faced by High School Technology Payakumbuh. The purpose of this research is to design tracer study application which can be accessed in real time by alumni as a medium for charging tracer study based on mobile data using Android studio application, and SQLite database as data storage media. The method used in this research is Spiral method. The focus of the research is to design the process consisting of making application architecture, activity model, mobile use case diagram, and mobile class diagram. The design of application interface for alumni consists of registration page, alumni login, main menu, edit alumni data and filling questionnaire, while the application interface design for BAAK consists of login page, dashboard menu, tracer study recapitulation and response rate. Alpha application testing using blackbox testing. The test results obtained some functions and modules and interfaces can run well and can facilitate the BAAK in collecting data graduates / alumni to complete the data required in the Institution Accreditation Form and study program. Subsequent research suggested the addition of an alumni consultation feature, and testing was conducted in beta.